THE EFFECTS OF STRATEGY TRAINING ON THE REALIZATION OF COMMUNICATIONSTRATEGIES IN AN EFL CLASS - Muhammad Sukircan, - (2011)
This research is largely experimental involving 23 students. Meanwhile, the data concerning the students' responses to the training were collected from observation and interview after the training. Descriptive qualitative analysis was used to analyze the linguistic features, consciousness of the strategy used, and the students' responses to the training, while quantitative analysis of matched t-test was used to analyze the frequency occurrences, number of circumlocution, and level of speech comprehensibility. In order to reveal the effects of strategy training, the data obtained before and after the training were compared. The results of the research reveal that (1) there is an increase in the number of types of linguistic features of CSs; (2) the frequency occurrence of CSs increases in several strategies (i.e. approximation, circumlocution, exemplification, and non-verbal), which implies positive effect, and decreases in several strategies (i.e. comparison, code-witching, foreignizing, repetition, avoidance, time-stalling device, and appeal for assistance), which also indicates positive effect, and remain constant in one strategy (i.e. word coinage); (3) there is significant increase in the number of circumlocutions; (4) there is significant increase in the level of speech comprehensibility; and (5) the students were conscious to select particular type of CSs. The results of the research also show that (6) the students actively participated in strategy training; and (7) the students feel that strategy training is useful to develop communication skills. The present study concludes that strategy training affects the realization of CSs in terms of linguistic features of CSs, frequency occurrence of CSs, level of speech comprehensibility, and consciousness of the strategies used. It is also found that the students show positive attitude toward the strategy training. Therefore, strategy training is recommended for enhancing students' communicative competence. Teaching CSs can develop the students' communication skills if the teacher provides the students with proper teaching materials and communication activities in the class.